Investigation of glutamatergic synapse genes in schizophrenia susceptibility : from linkage to genome-wide association studies - Gilks, William (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Psychiatry, 2011)
Schizophrenia is a common and severe mental illness which is highly heritable. Susceptibility to schizophrenia is likely to be caused by multiple genetic variants in combination with environmental risk factors. The identification of such genetic variants would greatly improve diagnosis and treatment. The first aim of this study was to identify common susceptibility variants for schizophrenia using a candidate gene case-control association study design. Nine genes were selected based upon positional (linkage data) and functional criteria (ARHGEF11, CNDP1, GGCX, GLUL, H0MER2, HTRA2, MAPT, PEA15 and SYNGAP1). Sixty-six tagging SNPs were tested in 375 schizophrenia cases and 812 controls from Ireland. Significant associations were identified at five SNPs in three of the genes (CNDP1, H0MER2, SYNGAP1). The second aim was to follow-up significant association findings at H0MER2 with fine- mapping, functional studies and independent replication. The strongest associated SNR at H0MER2 (rs2306428; p=0.006, OR=0.61) which was predicted to effect splicing. Replication analysis in the International Schizophrenia Consortium (ISC) sample (1,287 cases and 1,129 controls) was supportive of a role for rs2306428 in schizophrenia susceptibility (p=0.019, OR=0.77). No relationship was identified between genotype of rs2306428 and transcript levels in lymphoblast cells, nor on indices of neurocognitive function which were tested under the endophenotype hypothesis.
Keywords: Psychiatry, Ph.D.; Ph.D. Trinity College Dublin